2021
DOI: 10.1080/13880209.2021.1917626
|View full text |Cite
|
Sign up to set email alerts
|

Myrtenol improves brain damage and promotes angiogenesis in rats with cerebral infarction by activating the ERK1/2 signalling pathway

Abstract: Context: Cerebral ischaemia/reperfusion (I/R) injury has a high disability and fatality worldwide. Myrtenol has protective effects on myocardial I/R injury through antioxidant and anti-apoptotic effects.Objective: This study investigated the effect of myrtenol on cerebral ischaemia/reperfusion (I/R) injury and the underlying mechanism. Materials and methods: Cerebral I/R injury was induced in adult Sprague-Dawley rats by middle cerebral artery occlusion (MCAO) for 90 min. MCAO rats were treated with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The anxiolytic effects of myrtenol have been demonstrated in some tasks, including open field, plus maze, and light-dark compartment tasks [29,77]. It seems that myrtenol's effects on CNS are driven by the ease with which it can cross the blood-cerebrospinal barrier [73,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…The anxiolytic effects of myrtenol have been demonstrated in some tasks, including open field, plus maze, and light-dark compartment tasks [29,77]. It seems that myrtenol's effects on CNS are driven by the ease with which it can cross the blood-cerebrospinal barrier [73,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of toxicity of terpenes [ 56 , 57 ] makes them a harmless and potential therapeutic agent to increase the efficiency of the treatment of bacterial and fungal infections mediated by resistant strains. Thus, in much previous research, neither cytotoxicity nor acute toxicity on animals has been found for relatively high concentrations of myrtenol, up to 600 mg/L in vitro and 1.3 g per kg in vivo [ 58 , 59 , 60 ]. It is worth mentioning that a crucial benefit from using the described compounds is that their resource is almost inexhaustible [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the main sources of search is natural products and their derivatives, such as bicyclic monoterpene alcohols that have been shown to have several biological effects in the literature. (Nikitina et al, 2021) (-) Myrtenol is an example of this group with several reported biological effects in literature: angiogenesis (Huang et al, 2021), gastric protector (Viana et al, 2019), anti-bacterial (Cordeiro et al, 2020). Thus, the aim of this study was to examine the effects of myrtenol alone and in combination with antifungal drugs against Candida spp.…”
Section: Introductionmentioning
confidence: 99%